Exploring factors that influence staff turnover: A case study of a Chinese new venture - WEI, ZHUOYAN (2018)
In the 21st century, the essence of enterprise competition is competing for talent, and human resource is playing an increasingly significant role in organizational competition and development. However, as more jobs are available to choose from and due to the change of employment view, people no longer pursue stability, but adjust their work to be at any time according to their wishes and plans, which means that staff turnover has become higher. High staff turnover is more likely to cause huge losses to internal management as well as due to external competition. So, in order to keep human capital, companies are now paying more attention to the problem of staff turnover and are trying their best to retain indispensable staff. In China, because of the National Policy's strong support of entrepreneurship, the number of new ventures has increased in recent years. Talented staff is vital for the survival and development of these new ventures, and the negative impact of staff turnover is particularly evident in new ventures, where staff often have multiple roles or tasks. So, the purpose of this research is to explore the causes of new ventures’ staff turnover in China. This research uses qualitative research methods, through interviews with existing and terminated staff in a new venture in China, whereby many detailed reasons for new ventures’ staff turnover can be derived. This research is meaningful for new ventures to help them retain talented staff and this might be helpful to reduce the influence caused by staff turnover in new ventures.